Applying a practice lens to strategic information systems planning : a senior management perspective - Hughes, Jeffrey (Trinity College (Dublin, Ireland). Trinity Business School, 2015)
This study examines the practice of strategic information systems (SISP) planning by senior managers. The research topic was initially formed by the researcher's keen interest in the strategy and information systems (IS) fields. Upon reviewing the extant literature in the SISP domain, it became apparent that the literature was lacking in empirical investigations that shed light upon the 'doing' of SISP by its principal practitioners of senior managers. This led the researcher to a review of the strategy as practice (SAP) domain, with its inherent proclivity towards the activity that encompasses strategising. The SAP perspective's ability to uncover the realised praxis that comprises the work of strategising proved a compelling tool.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin.